Perilaku Menonton dan Kepuasan Petani terhadap Program Merajut Asa di Televisi TV Trans7 - Nurlaila Kusuma; Hadiyanto Hadiyanto (Jurnal Penyuluhan, 2015)
This study aims to identify the behavior of the audience watching television, as well as analyzed the relationship between viewing behavior with the level of audiences satisfaction the programs Merajut Asa TV Trans7. The method was used in this study is a survey method with the quantitative approaches supported by qualitative data. The results of this study explain the choice of the most popular by farmers is the program information and entertainment. Farmers have a low duration of watching television, i.e. during 7,50-45,75 minutes/day, as well as the duration of watching programs Merajut Asa TV Trans7 also low, i.e. during 1-15 minutes. Farmers have a low frequency of watching television, the only watch 1-4 times a week. Frequency of watching programs Merajut Asa TV Trans7 also low, i.e. 1-2 times a month. Duration of watching is not associated with the level of audiences satisfaction. Frequency of watching associated with the level of audiences satisfaction, i.e. satisfaction information.Keywords: viewing behavior, viewing satisfaction, merajut asa program, TV